Age and gender related neuromuscular pattern during trunk flexion-extension in chronic low back pain patients. Issue 1 (December 2016) - Kienbacher, Thomas; Fehrmann, Elisabeth; Habenicht, Richard; Koller, Daniela; Oeffel, Christian; Kollmitzer, Josef; Mair, Patrick; Ebenbichler, Gerold
Abstract Background The root mean square surface electromyographic activity of lumbar extensor muscles during dynamic trunk flexion and extension from standing has repeatedly been recommended to objectively assess muscle function in chronic low back pain patients. However, literature addressing older patients is sparse. This cross sectional study sought to examine differences in neuromuscular activation between age groups (>60 versus 40-60 versus <40 years) and sexes during a standardized trunk flexion-extension task. Methods A total of 216 patients (62 older, 84 middle-aged, 70 younger) performed maximum trunk extensions followed by trunk flexion extension testing thereby holding static positions at standing, half, and full trunk flexion. The lumbar extensor muscle activity and 3d-accelerometric signals intended to monitor hip and trunk position angles were recorded from the L5 (multifidus) and T4 (semispinalis thoracis) levels. Permutation ANOVA with bootstrapped confidence intervals were performed to examine for age and gender related differences. Ridge-regressions investigated the impact of physical-functional and psychological variables to the half flexion relaxation ratio (i.e. muscle activity at the half divided by that in maximum flexion position). Results Maximum back extension torque was slightly but significantly higher in youngest compared to oldest patients if male and females were pooled. Normalized RMS-SEMG revealed highest lumbar extensor muscle activity at standing in the oldest and the female groups. Patients over 60 years showed lowest activity changes from standing to half (increments) and from half to the maximum flexion position (decrements) leading to a significantly lower half flexion relaxation ratio compared to the youngest patients. These oldest patients demonstrated the highest hip and lowest lumbothoracic changes of position angles. Females had higher regional hip and gross trunk ranges of movement compared to males. Lumbothoracic flexion and the muscle activity at standing had a significant impact on the half flexion relaxation ratio. Conclusions The neuromuscular activation pattern and the kinematics in this trunk flexion-extension task involving static half flexion position changed according to age and sex. The test has a good potential to discriminate between impaired and unimpaired neuromuscular regulation of back extensors in cLBP patients, thereby allowing the design of more individualized exercise programs.